Research progress on effects of traditional Chinese medicine on myocardial ischemia–reperfusion injury: A review - Xing, Na; Long, Xiao-Tong; Zhang, Hui-Juan; Fu, Li-Dan; Huang, Jian-Yuan; Chaurembo, Abdallah Iddy; Chanda, Francis; Xu, Yun-Jing; Shu, Chi; Lin, Kai-Xuan; Yang, Ke; Lin, Han-Bin (Frontiers in Pharmacology, 2022)
Ischemic heart disease (IHD) is a high-risk disease in the middle-aged and elderly population. The ischemic heart may be further damaged after reperfusion therapy with percutaneous coronary intervention (PCI) and other methods, namely, myocardial ischemia–reperfusion injury (MIRI), which further affects revascularization and hinders patient rehabilitation. Therefore, the investigation of new therapies against MIRI has drawn great global attention. Within the long history of the prevention and treatment of MIRI, traditional Chinese medicine (TCM) has increasingly been recognized by the scientific community for its multi-component and multi-target effects. These multi-target effects provide a conspicuous advantage to the anti-MIRI of TCM to overcome the shortcomings of single-component drugs, thereby pointing toward a novel avenue for the treatment of MIRI. However, very few reviews have summarized the currently available anti-MIRI of TCM. Therefore, a systematic data mining of TCM for protecting against MIRI will certainly accelerate the processes of drug discovery and help to identify safe candidates with synergistic formulations. The present review aims to describe TCM-based research in MIRI treatment through electronic retrieval of articles, patents, and ethnopharmacology documents. This review reported the progress of research on the active ingredients, efficacy, and underlying mechanism of anti-MIRI in TCM and TCM formulas, provided scientific support to the clinical use of TCM in the treatment of MIRI, and revealed the corresponding clinical significance and development prospects of TCM in treating MIRI.